Carrying Capacity Based on Chlorophyll-ain The Betung Lake Betung Village PangkalanKuras Sub-districtPelalawan District Riau Province - Diah Sari Ninggrum; Asmika Harnalin Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractCarrying capacity is defined as the ability of aquatic environment to support the life of organism in that area. A study aimed to assess the aquatic carrying capacity for extensive fishing in the Betung lake, Betung Village, Pangkalan Kuras Sub-district Pelalawan District, Riau Province. The carrying capacity was determined based on primary productivity using chlorophyll-aconcentration.This research was conducted July-August 2019. There were 3 stations, namely Station 1 (inlet area), Station 2 (in the middle of the lake) and Station 3 (in the end of the lake). In each stations, there were 2 sampling point, in the surface (15 cm) and 2 Secchi (160 cm) depth. Sampling was done three times, once a week. Water quality parameters measured werechlorophyll-a, transparency, temperature, pH, dissolved oxygen, CO2, nitrate and phosphate concentration. Results shown that chlorophyll-a:17.81-26.73 µg/L, transparency : 81.3-84 cm, temperature : 28.3-29.7ºC, pH: 5, dissolved oxygen : 3.87-6.12 mg/L, CO2 : 6.27-15.42 mg/L,nitrate : 0.02-0.05 mg/L, and phosphate : 0.02-0.04 mg/L. Based on chlorophyll-a concentration, the carrying capacity in Betung Lake was 1.61 tons/fish/year.Keyword: Oxbow lake, Primary Productivity, and Water quality